2018
DOI: 10.7150/jca.23344
|View full text |Cite
|
Sign up to set email alerts
|

Nomograms to Predict Individual Prognosis of Patients with Primary Small Cell Carcinoma of the Bladder

Abstract: Objectives: To develop reliable nomograms to estimate individualized overall survival (OS) and cancer specific survival (CSS) for patients with primary small cell carcinoma of the bladder (SCCB) and compare the predictive value with the AJCC stages.Patients and Methods: 582 eligible SCCB patients identified in the Surveillance, Epidemiology, and End Results (SEER) dataset were randomly divided into training (n=482) and validation (n=100) cohorts. Akaike information criterion was used to select the clinically i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 47 publications
3
53
0
Order By: Relevance
“…The NRI and IDI are more sensitive indicators than the C-index, and the NRI indicated that the proposed model reclassified the risk probabilities better than did the AJCC staging system, while the IDI demonstrated the superior ability of the constructed nomogram to distinguish cases compared with the AJCC staging system. Numerous previous studies have found benefits of applying DCA [29][30][31][32][33], and the results of the current study showed that the 3-, 5-, and 10-year DCA curves displayed net benefits larger than those of the AJCC staging system, both in the training set and validation set (Fig. 4).…”
Section: Discussionsupporting
confidence: 66%
“…The NRI and IDI are more sensitive indicators than the C-index, and the NRI indicated that the proposed model reclassified the risk probabilities better than did the AJCC staging system, while the IDI demonstrated the superior ability of the constructed nomogram to distinguish cases compared with the AJCC staging system. Numerous previous studies have found benefits of applying DCA [29][30][31][32][33], and the results of the current study showed that the 3-, 5-, and 10-year DCA curves displayed net benefits larger than those of the AJCC staging system, both in the training set and validation set (Fig. 4).…”
Section: Discussionsupporting
confidence: 66%
“…[5][6][7][8] M2 macrophages secrete various anti-in ammatory molecules that can inhibit the immune system and promote tumor angiogenesis, proliferation, invasion, and metastasis, and prevent apoptosis. 5,10,11 M2 macrophage surface markers include CD163, Stabilin-1, and CD206. 4,9,10 Although some studies have explored the correlation between intertumoral macrophages and prognosis, [2][3][4][5] the results were heterogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, nomograms are widely applied in major types of cancer. [6][7][8][9][10][11] In addition, nomograms are preferred compared with traditional staging systems for many types of cancer. It is because of the intuitive and easy-to-understand features of nomograms that they have gradually received more and more attention in medical research and clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…The nomogram model can quantify, graph, and visualize Logistic regression results to achieve individualized prediction of disease risk. It has been successfully used in clinical diagnosis and prognostic assessment of various diseases [6,7].…”
Section: Introductionmentioning
confidence: 99%